Melammu: The Ancient World in an Age of Globalization - Markham J. Geller (ed.) (Proceedings 7: Max Planck Research Library for the History and Development of Knowledge, 2014)
Melammu volumes have broadened the horizons of studies of antiquity by encouraging the crossing of geographical and cultural boundaries between ancient civilizations of the Mediterranean and Near East. The present Melammu volume extends from Greece to India, with articles on Phrygia and Armenia, also viewing texts from ancient Israel, Egypt, and Mesopotamia. The globalization described in this volume extends over language barriers and literatures, showing how texts as well as goods can travel between societies and regions. This collection of papers offer new insights and perspectives into connections between the Mediterranean World, Mesopotamia, Anatolia, Persia and India.